1996
DOI: 10.1037/0022-3514.70.4.713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perspective taking on the cognitive representation of persons: A merging of self and other.

Abstract: Two experiments examined the possibility that perspective taking leads observers to create cognitive representation of others that substantially overlap with the observers' own self-representations. In Experiment 1 observers receiving role-taking instructions were more likely to ascribe traits to a novel target that they (observers) had earlier indicated were self-descriptive. This pattern was most pronounced, however for positively valenced traits. In Experiment 2 some participants received role-taking instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
614
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 650 publications
(673 citation statements)
references
References 22 publications
30
614
2
3
Order By: Relevance
“…Goldman (1989Goldman ( /1995 has stressed that our attempts to understand others by simulating how we would feel in their position can both exhibit automaticity and be influenced by previous efforts. With such a view, there will be times when the perspective-taking process (or parts of it) runs relatively easily or with minimally-reported cognitive effort, while at other times it may be subjectively felt as less easy, more conscious, and/or called upon (Davis et al, 1996;Fennis, 2011;Roβnagel, 2000). It is likely that the latter situations are the type discussed by many of our participants.…”
Section: Behaviours and Resolutionmentioning
confidence: 89%
See 1 more Smart Citation
“…Goldman (1989Goldman ( /1995 has stressed that our attempts to understand others by simulating how we would feel in their position can both exhibit automaticity and be influenced by previous efforts. With such a view, there will be times when the perspective-taking process (or parts of it) runs relatively easily or with minimally-reported cognitive effort, while at other times it may be subjectively felt as less easy, more conscious, and/or called upon (Davis et al, 1996;Fennis, 2011;Roβnagel, 2000). It is likely that the latter situations are the type discussed by many of our participants.…”
Section: Behaviours and Resolutionmentioning
confidence: 89%
“…Davis, Conklin, Smith, and Luce (1996) suggested that in the process of taking another's perspective the person's mental representations of self and target become more similar.…”
Section: The Process Of Perspective Takingmentioning
confidence: 99%
“…Furthermore, we found no differences between the two perspective-taking conditions-a pattern that was confirmed by the results of the manipulation check, which indicated that participants did not distinguish between the two perspective-taking instruction sets. Although some previous research has demonstrated important emotional, cognitive, motivational, and neurophysiological differences when comparing these two perspective-taking conditions (Batson, 2009), numerous other studies have observed null effects (Davis et al, 1996, Experiment 1; Davis et al, 2004, Experiment 2;Finlay & Stephan, 2000;Galinsky, Wang, & Ku, 2008, Experiment 2a). Batson (2009) has argued that null effects are especially likely when participants have very limited information about the target whose perspective they are asked to adopt, though this was not necessarily the case in Experiment 1 or in Finlay and Stephan's (2000) study.…”
Section: Automatic Interracial Evaluationsmentioning
confidence: 99%
“…Some participants tried to imagine the Black man's thoughts, feelings, and experiences ( perspective-taking-other condition) as they watched the video; others tried to imagine their own thoughts, feelings, and experiences as if they were in the Black man's situation ( perspectivetaking-self condition). Because both approaches have been used in past research (e.g., Batson, Early, & Salvarini, 1997;Davis, Conklin, Smith, & Luce, 1996;Galinsky, Wang, & Ku, 2008) and, in some cases, have been found to have different psychological consequences (Batson, 2009), we wanted to explore whether the specific form of perspective taking would qualify our results. After watching the video, participants completed a variant of the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998) that assesses automatic evaluations of Black Americans relative to White Americans (i.e., personalized evaluative race IAT; Olson & Fazio, 2004).…”
Section: Experiments 1: Automatic Interracial Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation